A New Systemic Safety Detecting Software - Xilong Qu; Yingjun Wang (Institute of Advanced Engineering and Science, 2014)
Because it is hard to find and to clear cockhorse and virus developed by root kit technology, antivirus soft at present is hard to clear virus in the system, which make the system in dangers status of hazard. So, designing a speedy clear Trojan and virus makes by root kit is very important. The article.is based on SDK, adopting the technology.of kernel to design the Clairvoyant systemic safety detecting software. It major function is monitors.the service of the system and the operation. Monitor the register changer. Search the file, process, system module hided by the virus. It can also end protected processes and delete protected files forcibly. Through the port.mapping of processes, it can find.port messages opened.by system, processes opening ports and.cockhorse effectively. http://dx.doi.org/10.11591/telkomnika.v12i10.5345